ANALISIS KINERJA AC-WC (ASPHALT CONCRETE-WEARING COURSE) MENGGUNAKAN RESIN LYCAL DITINJAU DARI PARAMETER MARSHALL (PERFORMANCE ANALYSIS OF AC-WC - Samudro, Revan Aji; Rahardjo, Boedi; -, Pranoto (Direktorat Bina Teknik Jalan dan Jembatan, 2024)
Road damage is a common problem encountered by road users. As the volume of vehicles increases, the roads become more easily damaged. In addition, the increasing number of cars with loads exceeding the planned load capacity of the road can also shorten the strength life of the road. The AC-WC layer has the potential to be damaged because it often receives direct pressure and friction from the vehicle. The asphalt quality has to be improved to overcome the damage of AC-WC asphalt pavement. Modified asphalt applied to the manufacture of AC-WC can be used to enhance pavement quality. This research aims to investigate the performance of AC-WC with the addition of lycal resin in terms of the Marshall Parameters. The research design begins with preparing and testing the constituent materials used and lycal resin, then making test specimens with optimum bitumen content, then making Marshall test specimens with the addition of lycal resin polymer with respective levels of 0%, 1%, 2%, 3%, and 4%. The results of the Marshall test were compared to the stability, flow, MQ, VIM, VMA, and VFA values. The Marshall's test result complies with the 2018 Bina Marga General Specifications for Road and Bridge Construction Works (Revision 2). Keywords: lycal resin, Marshall parameters, AC-WC, pavement, asphalt